Emotional Decision-Making and Word Processing Among Bilingual Speakers - Stankovic, Michelle (Curtin University, 2024)
This research investigates how bilinguals process emotion in their first and second language. It explores whether differences in bilingual profiles affect moral decision-making and emotional word processing, examining the impact of proficiency, age of acquisition, language use and immersion. Findings suggest not all bilinguals experience reduced emotions in their second language. Proficient bilinguals with extensive language use and immersion may process emotions similarly across languages, indicating a more integrated and embodied cognitive system.